Managing Sales Forecasters - Bert de Bruijn; Philip Hans Franses (Tinbergen Institute, 2012)
A Forecast Support System (FSS), which generates sales forecasts, is a sophisticated business analytical tool that can help to improve targeted business decisions. Many companies use such a tool, although at the same time they may allow managers to quote their own forecasts. These sales forecasters (managers) can take the FSS output as their input, but they can also fully ignore the FSS out- comes. We propose a methodology that allows to evaluate the forecast accuracy of these managers, relative to the FSS, while taking aboard latent variation across managers' behavior. We show that the results, here for a large Germany-based pharmaceutical company, can in fact be used to manage the sales forecasters by giving clear-cut recommendations for improvement.
urn:NBN:nl:ui:15-1765/38213
Keywords: M11; M31; 330; Forecast Support System; Sales forecasters; Forecast accuracy; Absatz; Prognoseverfahren; Management-Informationssystem